Pertimbangan Hakim terhadap Penegakan Hukum Tindak Pidana Korupsi Dana Desa - Asmar, Ihsan; Azisa, Nur; Haeranah, Haeranah (Universitas Negeri Malang, 2021)
This study aimed to analyze law enforcement efforts against criminal acts of corruption and legal considerations of judges in deciding cases related to criminal acts of corruption in village funds. This type of research was empirical research. The data source came from data obtained directly from the community or commonly referred to as primary data and other data obtained from library materials or commonly referred to as secondary data. The analysis qualitative was used for analyzing data. Law enforcement against criminal acts of corruption in village funds carried out by the prosecutor’s office was still repressive. There were no preventive actions to educate the village government about the dangers of corruption. Enforcement of village funds corruption by the High Court still very weak even though the actions taken by law enforcers were in accordance by the provisions stipulated in the Corruption Crime Law. Judges’ considerations regarded law enforcement on criminal acts of corruption in village funds consisted of juridical and non-juridical considerations.